Predictors of viral suppression and rebound among HIV-positive men who have sex with men in a large multi-site Canadian cohort. Issue 1 (December 2016) - Tanner, Zachary; Lachowsky, Nathan; Ding, Erin; Samji, Hasina; Hull, Mark; Cescon, Angela; Patterson, Sophie; Chia, Jason; Leslie, Alia; Raboud, Janet; Loutfy, Mona; Cooper, Curtis; et al.
Abstract Background Gay, bisexual and other men who have sex with men (MSM) are disproportionately affected by HIV in Canada. Combination antiretroviral therapy has been shown to dramatically decrease progression to AIDS, premature death and HIV transmission. However, there are no comprehensive data regarding combination antiretroviral therapy outcomes among this population. We sought to identify socio-demographic and clinical correlates of viral suppression and rebound. Methods Our analysis included MSM participants in the Canadian Observational Cohort, a multi-site cohort of HIV-positive adults from Canada's three most populous provinces, aged ≥18 years who first initiated combination antiretroviral therapy between 2000 and 2011. We used accelerated failure time models to identify factors predicting time to suppression (2 measures <50 copies/mL ≥30 days apart) and subsequent rebound (2 measures >200 copies/mL ≥30 days apart). Results Of 2, 858 participants, 2, 448 (86 %) achieved viral suppression in a median time of 5 months (Q1–Q3: 3–7 months). Viral suppression was significantly associated with later calendar year of antiretroviral therapy initiation, no history of injection drug use, lower baseline viral load, being on an initial regimen consisting of non-nucleoside reverse-transcriptase inhibitors, and older age. Among those who suppressed, 295 (12 %) experienced viral rebound. This was associated with earlier calendar year of antiretroviral therapy initiation, injection drug use history, younger age, higher baseline CD4 cell count, and living in British Columbia. Conclusions Further strategies are required to optimize combination antiretroviral therapy outcomes in men who have sex with men in Canada, specifically targeting younger MSM and those with a history of injection drug use.